Cloud computing adoption in Small and Medium Enterprises (SMEs): A systematic literature review and directions for future research - Jayeola, Olakunle; Sidek, Shafie; Abd Rahman, Azmawani; Mahomed, Anuar Shah Bali; Hu, Jimin (Universiti Malaysia Sarawak, 2021)
This paper presents a systematic literature review of the current state of cloud computing adoption (CC) in small and medium enterprises (SMEs) with the main objective of providing insights into data analysis techniques, CC services being investigated, and further assessing studies and their associated theories/frameworks, publication trends and outlets, geographical distribution and the most important adoption factors over 10 years (2011-2020). Six databases were consulted for a total of 76 articles. The findings indicate that Partial Least Squares Structural Equation Modeling (PLS-SEM) and interpretative analysis were the most frequently used quantitative and qualitative data analysis techniques. Generic CC services were investigated more than specific CC business applications. The number of publications has fluctuated over the last decade, and the vast majority did not incorporate any underlying theory. The Journal of Small Business and Enterprise Development and IEEE conferences proceedings were major publication outlets. Asia recorded the highest number of studies, whereas cost savings is the most important adoption factor. This study contributes to CC research by providing deeper insights into data analysis techniques used, CC services investigated, and other crucial research issues of CC adoption in SMEs to guide future research directions and SMEs' cloud computing implementation.